Predicting the fracture initiation pressure for perforated water injection wells in fossil energy development. (21st June 2019) - Lu, Yu; Li, Haitao; Lu, Cong; Wu, Keliu; Chen, Zhangxin; Li, Jing; Tang, Xiaoxu; Huang, Xiaodong; Tang, Mingdeng
Abstract: Water injection is widely performed to enhance oil recovery in fossil energy development. The fracture initiation pressure (FIP) is a key parameter for designing the reasonable injection pressure for micro-fracturing water injection (MFWI). In this work, a modified method was presented to accurately predict the FIP, in which the thermal effect and plugging effect were considered; moreover, the stress around perforations was analyzed. To validate our method, the field tests, including a step rate test (SRT) and a well test, were conducted to obtain the actual FIP for perforated water injection wells, and then the FIP calculated by our method was compared with a low relative error of about 1.7%. Results show that (i) a greater temperature difference between the injected water and the formation forms a greater thermal stress around perforations, resulting in a greater change in the FIP; (ii) a larger skin factor causes a greater pressure drop for the injected water flowing through a plugged area, resulting in a stronger effective stress reduction around perforations and further producing a larger FIP. Therefore, our present work illustrates a better understanding of the stress distribution around a perforated wellbore, and paves a path for a more accurate prediction of the FIP in perforated water injection wells. Highlights: A model for predicting FIP in perforated water injection wells is proposed. A step rate test and well tests were conducted. A method for obtaining the actual FIP in perforated water injection wells is discussed. The proposed method performs with a lower relative error than the existing models.